Aminoacyl-tRNA Synthetases: On Anti-Synthetase Syndrome and Beyond - Galindo-Feria, Angeles S.; Notarnicola, Antonella; Lundberg, Ingrid E.; Horuluoglu, Begum (Frontiers in Immunology, 2022)
Anti-synthetase syndrome (ASSD) is an autoimmune disease characterized by the presence of autoantibodies targeting one of several aminoacyl t-RNA synthetases (aaRSs) along with clinical features including interstitial lung disease, myositis, Raynaud’s phenomenon, arthritis, mechanic´s hands and fever. The family of aaRSs consists of highly conserved cytoplasmic and mitochondrial enzymes, one for each amino acid, which are essential for the RNA translation machinery and protein synthesis. Along with their main functions, aaRSs are involved in the development of immune responses, regulation of transcription, and gene-specific silencing of translation. During the last decade, these proteins have been associated with cancer, neurological disorders, infectious responses and autoimmune diseases including ASSD. To date, several aaRSs have been described to be possible autoantigens in different diseases. The most commonly described are histidyl (HisRS), threonyl (ThrRS), alanyl (AlaRS), glycyl (GlyRS), isoleucyl (IleRS), asparaginyl (AsnRS), phenylalanyl (PheRS), tyrosyl (TyrRS), lysyl (LysRS), glutaminyl (GlnRS), tryptophanyl (TrpRS) and seryl (SerRS) tRNA synthetases. Autoantibodies against the first eight autoantigens listed above have been associated with ASSD while the rest with other diseases This review will address what is known about the function of the aaRSs with a focus on their autoantigenic properties. We will also describe the anti-aaRSs autoantibodies, their association to specific clinical manifestations, and discuss their potential contribution to the pathogenesis of ASSD.